Answer:
b. The student's scores on the posttest would have a smaller standard deviation.
Step-by-step explanation:
The first test is taken before the material is covered in class so we expect the standard deviation to be high because not everyone's scores would be lying close to the mean. Equal number of students mastered most, some or almost none of the material from reading the textbook based on the pretest result. this means the data is varying, so the standard deviation is large.
Whereas, after the teacher has taught the material and given the homework, they must have understood most of the material. The test they take after teaching as a post test. The results of the post test would have a smaller standard deviation as most of the students would have scored good. Hence, the student's scores on the posttest would have a smaller standard deviation.
Answer:
1. 3 7/12 (decimal: 3.583333)
2. -5 3/28
3. 2 29/40
4. −1 9
/14
Answer:
The answer is below
Step-by-step explanation:
Let S denote syntax errors and L denote logic errors.
Given that P(S) = 36% = 0.36, P(L) = 47% = 0.47, P(S ∪ L) = 56% = 0.56
a) The probability a program contains both error types = P(S ∩ L)
The probability that the programs contains only syntax error = P(S ∩ L') = P(S ∪ L) - P(L) = 56% - 47% = 9%
The probability that the programs contains only logic error = P(S' ∩ L) = P(S ∪ L) - P(S) = 56% - 36% = 20%
P(S ∩ L) = P(S ∪ L) - [P(S ∩ L') + P(S' ∩ L)] =56% - (9% + 20%) = 56% - 29% = 27%
b) Probability a program contains neither error type= P(S ∪ L)' = 1 - P(S ∪ L) = 1 - 0.56 = 0.44
c) The probability a program has logic errors, but not syntax errors = P(S' ∩ L) = P(S ∪ L) - P(S) = 56% - 36% = 20%
d) The probability a program either has no syntax errors or has no logic errors = P(S ∪ L)' = 1 - P(S ∪ L) = 1 - 0.56 = 0.44
Answer:
(x+7)(x-2)
Step-by-step explanation:
Multiply the second fraction by (x-2) so that the value of it doesn't change
Explanation:
using the parabola formula:
y = a(x-h)² + k²
vertex = (h, k)
We are given a parebola equation of: y = x²+9
comparing both equations to get the vertex:
y = y
a = 1
(x-h)² = x²
x² = (x + 0)²
(x-h)² = (x + 0)²
h = 0
+k = +9
k = 9
The vertex of the parabola as (x, y): (0, 9)